Academic Libraries Reflecting on Crisis, the Fourth Industrial Revolution and the Way Forward - Janse van Vuren, Anette (UJ Press, 2022)
As we begin to fundamentally redefine our world, informed through the Fourth Industrial Revolution (4IR) lens, entire industries are gearing up for this disruptive event. Library practices have been no exception. With the advent of advanced digital technology, knowledge is becoming more readily accessible. This book focuses on how libraries need to respond, adapt, and transform to become meaningful spaces in our rapidly changing 21st century, within the 4IR and coupled with the restrictions of the pandemic. Tracing the evolution of technology over the centuries, the changing role of the library as a response to disruptions is discussed.